Radical Functionalisation of Alkenes - Himmel, Leonard (2023)
A main objective in organic chemistry is the concise formation of C–C bonds, and the reaction between a carbon centred radical and an alkene moiety has emerged as a reliable method to this end. In this Thesis, we describe the reaction of carbon-centred radicals with alkenes to form a new C–C bond, and different methods were explored to convert the resulting radical intermediate into potentially valuable products or building blocks for further operations.